2015
DOI: 10.1016/j.pharmthera.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the tumor vasculature and oxygenation to improve therapy

Abstract: The tumor microenvironment is increasingly recognized as a major factor influencing the success of therapeutic treatments and has become a key focus for cancer research. The progressive growth of a tumor results in an inability of normal tissue blood vessels to oxygenate and provide sufficient nutritional support to tumor cells. As a consequence the expanding neoplastic cell population initiates its own vascular network which is both structurally and functionally abnormal. This aberrant vasculature impacts all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 215 publications
(279 reference statements)
1
107
0
2
Order By: Relevance
“…Hypoxic conditions are seen in solid tumors despite hypervascularization due to an imbalance between the rates of tumor cell proliferation, new endothelial cell formation, and disorganized vascular supply [4,5]. Hypoxia has been shown to affect the L-arginine metabolic pathway in various types of cells, including smooth muscle cells and endothelial cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic conditions are seen in solid tumors despite hypervascularization due to an imbalance between the rates of tumor cell proliferation, new endothelial cell formation, and disorganized vascular supply [4,5]. Hypoxia has been shown to affect the L-arginine metabolic pathway in various types of cells, including smooth muscle cells and endothelial cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…There may be a lot of possible mechanisms accountable for this effect. One of the most important explanation is "Normalization of tumor vasculature", the VEGF Trap and BEV can improve the tumor microenvironment of interstitial hypertension, hypoxia and acidosis, leading to more efficient delivery of TMZ and oxygen to tumor cells 14,15 . A second possible mechanism is that by reducing vascular permeability, the VEGF Trap and BEV can prevent many serum-derived growth factors that promote tumor cell survival from reaching the tumor parenchyma, thus slowing down tumor cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a large number of studies have shown that the efficacy of anti-angiogenic therapy alone was limited and the better therapeutic effects could be achieved in association with chemotherapy. This may be due to that the anti-angiogenic drugs can reestablish the tumor vasculature, normalize the tumor vessels and improve the delivery of drugs within the tumor 14,15 . Thus, we also combined AAV2-VEGF-Trap with TMZ to explore the antitumor effects and determine whether there is a synergistic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, significant differences exist between physiological vessels and vessels in the tumor microenvironment. 9 The normal vasculature is a wellorganized network that is strictly controlled by a balance between proangiogenic and antiangiogenic factors and is arranged in a hierarchy of well-differentiated arteries, arterioles, capillaries, venules, and veins. In contrast, the overexpression of proangiogenic factors in the tumor environment results in an unevenly distributed and chaotic vasculature with irregular branches and the formation of arteriovenous shunts.…”
Section: Vascular Disrupting Agents (Vdas)mentioning
confidence: 99%